A Marketing Booklet for Brotherwood Decoration: A Way to Promote This New Company and Its Products to Its Prospective Customers - Devina Wijaya Halim; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
Brotherwood Decoration is a new decoration company based in Surabaya which uses recycled wood as the main material. This Company was just recently established in June 2014. As a new decoration company, there are only a few people who know about this company. Moreover, there are also some decoration companies which are bigger and more experienced than Brotherwood Decoration. Unlike its predecessors, Brotherwood Decoration, as a new company, is less known. Because of that, it does not have as many customers as its predecessors. Therefore, it is better for Brotherwood Decoration to start showing its strengths to more people. To accomplish the goal, a marketing booklet is the best solution to solve the problem in Brotherwood Decoration. There are four parts in this marketing booklet: table of contents, company overview (“About Brotherwood Decoration”), products (“Products”), and company contact information (“Contact Us”). By having these information, the marketing booklet will be able to help Brotherwood Decoration in introducing its hotel, getting more customers, increasing its revenues, and becoming a big decoration company